Staging international communism: British–Australian radical theatre connections. Issue 4 (2nd October 2019) - Milner, Lisa; Brigden, Cathy
ABSTRACT: Encouraged by Communist parties and left-wing trade unions, radical, or working-class, theatre groups of the twentieth century were crucial in the development of a long-lasting left-wing cultural activist impulse in a number of nations. The branches of the Unity Theatre in UK and the New Theatre in Australia had a highly conscious democratic and explicit working class orientation, and presented various combinations of mainstream and radical dramatic genres and plays. Drawing on oral histories and archival research, this chapter explores the politics of popular culture by focusing on the degrees of mobility of ideas, dramatic texts and people and politics between the two theatres. The emergent mobility patterns across these elements demonstrated the effect of 'tyranny of distance' to invoke Blainey's phrase1 and the sociocultural mores of 'Empire' on those transnational flows. Whether it was the mobility of ideas, texts or people, a more complex picture emerged than simple exchange or reciprocal influence. Informing our discussion is the mobility studies literature, following the 'mobility turn' in the social sciences. A number of concepts within mobility studies provide a lens for analysing the movement of ideas, scripts and people between Unity and the New Theatre.